Fundamental Tax Reform in The Netherlands - Sijbren Cnossen; Lans Bovenberg (Center for Economic Studies and ifo Institute (CESifo), 2000)
The Dutch Parliament has passed legislation for a new income tax that abolishes the current tax on personal capital income and substitutes it by a presumptive capital income tax, which is in fact a net wealth tax. This paper contrasts this wealth tax with a conventional realization-based capital gains tax, a retrospective capital gains tax which attempts to charge interest on the deferred tax, and a capital accretion tax which taxes capital gains as they accrue. None of the approaches meets all criteria for a 'good' income tax, i.e., equity, efficiency, and administrative feasibility. We thus conclude that the effective and neutral taxation of capital income can best be ensured through a combination of (a) a capital accretion tax to capture the returns on easy-to-value financial products, (b) a capital gains tax with interest to tax the returns on hard-to-value real estate and small businesses, and (c) a broad presumptive capital income tax, i.e., a net wealth tax, to account for the utility of holding wealth. We favor uniform and moderate proportional tax rates in the context of a dual income tax under which capital income is taxed separately from labor income.
Keywords: 330; Capital income taxation; capital gains taxation; tax reform; wealth tax